HypExp 2, expanding hypergeometric functions about half-integer parameters - Huber, Tobias; Maître, Daniel (Computer physics communications, 2012)
HypExp is a Mathematica package for expanding hypergeometric functions about integer and half-integer parameters. Program title: HypExp 2 Catalogue identifier: ADXF_v2_1 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/ADXF_v2_1.html Program obtainable from: CPC Program Library, Queenʼs University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 107 274 No. of bytes in distributed program, including test data, etc.: 2 690 337 Distribution format: tar.gz Programming language: Mathematica 7 and 8 Computer: Computers running Mathematica Operating system: Linux, Windows, Mac RAM: Depending on the complexity of the problem Supplementary material: Library files which contain the expansion of certain hypergeometric functions around their parameters are available Classification: 4.7, 5 Catalogue identifier of previous version: ADXF_v2_0 Journal reference of previous version: Comput. Phys. Comm. 178 (2008) 755 Does the new version supersede the previous version?: Yes Nature of problem: Expansion of hypergeometric functions about parameters that are integer and/or half-integer valued. Solution method: New algorithm implemented in Mathematica. Reasons for new version: Compatibility with new versions of Mathematica. Summary of revisions: Support for versions 7 and 8 of Mathematica added. No changes in the features of the package. Restrictions: The classes of hypergeometric functions with half-integer parameters that can be expanded are listed in the long write-up. Additional comments: The package uses the package HPL included in the distribution. Running time: Depending on the expansion.